THE TOMSK SCIENTIFIC SCHOOL OF NEUROLOGISTS. TO THE 120TH ANNIVERSARY OF THE DEPARTMENT OF NEUROLOGY AND NEUROSURGERY OF SIBERIAN STATE MEDICAL UNIVERSITY - V. M. Alifirova; M. N. Azhermacheva (Бюллетень сибирской медицины)
The history of the development of the Tomsk Scientific School Neurologists and the past and current events in the Department of Neurology and Neurosurgery of Siberian State Medical University are described. The Department of Neurology was established in 1881–1882. At a different times the department was headed by many great Russian physicians such as Michail G. Kurlov, Leonid I. Omorokov, Nikolay V. Schubin, Nikolay I. Komandenko. In addition to the academic work the department leads research in many fields of neurology, including movement disorders, cerebrovascular diseases, demyelinating and paroxysmal diseases.